2013
DOI: 10.1021/ol403370t
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Synthesis of Ynones from Acyl Chlorides and Potassium Alkynyltrifluoroborate Salts

Abstract: Ynones are a valuable functional group and building block in organic synthesis. Ynones serve as a precursor to many important organic functional groups and scaffolds. Traditional methods for the preparation of ynones are associated with drawbacks including harsh conditions, multiple purification steps, and the presence of unwanted byproducts. An alternative method for the straightforward preparation of ynones from acyl chlorides and potassium alkynyltrifluoroborate salts is described herein. The adoption of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 49 publications
0
22
0
1
Order By: Relevance
“…Compound 3 could be converted to the desired ynone intermediate (Scheme 3). 28 Unfortunately, conditions for the conversion of 2-3 resulted in partial decomposition making isolation of clean product a challenge. Additionally, this method is not ideal as a result of the number of steps required for the preparation of acyl chloride.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 3 could be converted to the desired ynone intermediate (Scheme 3). 28 Unfortunately, conditions for the conversion of 2-3 resulted in partial decomposition making isolation of clean product a challenge. Additionally, this method is not ideal as a result of the number of steps required for the preparation of acyl chloride.…”
Section: Resultsmentioning
confidence: 99%
“…27 Previously, we have developed a straightforward procedure for the preparation of ynones from acyl chlorides and potassium alkynyltrifluoroborate salts (Scheme 2). 28 This convenient, one-pot reaction proceeds rapidly in the presence of boron trichloride without exclusion of air or moisture. Furthermore, alkynyltrifluoroborate salts can be easily prepared from terminal alkynes according to the published procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Unless otherwise noted, all reagents were obtained from Sigma-Aldrich (Oakville, ON, Canada or Milwaukee, WI, USA) and used without further purification. Potassium trifluoroborate salts were synthesized according to published procedures [4,5,16,50,51]. Reaction progress was monitored via thin layer chromatography (TLC) on silica gel (60 Å) with visualization using ultraviolet light (254 nm) and by staining with phosphomolybdic acid (PMA).…”
Section: General Synthetic Methodsmentioning
confidence: 99%
“…Potassium alkynyltrifluoroborate salts were prepared according to known procedures [4,5,16,51]. To a solution of the indicated terminal alkyne (1.0 equiv.)…”
Section: General Procedures For the Synthesis Of Alkynyl Potassium Orgmentioning
confidence: 99%
“…Furthermore, the transition metal catalyzed cross coupling of acid chlorides with terminal alkynes is a common route toward alkynyl ketones [4]. Recently, transition metal free Lewis acid catalyzed reaction of alkynyltrifluoroborate salts with acid chloride has been reported for the synthesis of alkynyl ketones [5]. Tang et al have reported the synthesis of alkynyl ketones using Pd(OAc) 2 /bis[ (2-diphenylphosphino) phenyl] ether catalyst and tert-butyl isocyanide as a carbonylating reagent [6].…”
Section: Introductionmentioning
confidence: 99%